Palbociclib as single agent or in combination with the endocrine therapy received before disease progression for estrogen receptor-positive, HER2-negative metastatic breast cancer: TREnd trial. (11th June 2018) - Malorni, L; Curigliano, G; Minisini, A M; Cinieri, S; Tondini, C A; D'Hollander, K; Arpino, G; Bernardo, A; Martignetti, A; Criscitiello, C; Puglisi, F; Pestrin, M; et al.
Abstract: Background: The activity of palbociclib as a single agent in advanced breast cancer has not been extensively studied, with the only available clinical data limited to heavily pretreated patients. Preclinical data suggests palbociclib may partially reverse endocrine resistance, though this hypothesis has not been evaluated in previous clinical studies. This phase II, open-label, multicenter study examined the activity of palbociclib monotherapy, as well as palbociclib given in combination with the same endocrine therapy (ET) that was received prior to disease progression, in postmenopausal women with moderately pretreated, estrogen receptor-positive, HER2 negative advanced breast cancer. Patients and methods: Eligible women with advanced disease which had progressed on one or two prior ETs were randomized 1 : 1 to receive either palbociclib alone, or palbociclib in combination with the ET as previously received. Primary end point was clinical benefit rate (CBR); secondary end points included progression-free survival (PFS). Results: Between October 2012 and July 2016, a total of 115 patients were randomized. The CBR was 54% [95% confidence interval (CI): 41.5–63.7] for combination therapy, and 60% (95% CI: 47.8–72.9) for monotherapy. Median PFS was 10.8 months (95% CI: 5.6–12.7) for combination therapy, and 6.5 months (95% CI: 5.4–8.5) for monotherapy [hazard ratio (HR) 0.69; 95% CI: 0.4–1.1, exploratory P -value = 0.12]. Exploratory analyses revealed the PFS advantage for combination therapy was seen in the subgroup of patients who received prior ET for >6 months (HR 0.53; 95% CI: 0.3–0.9, exploratory P -value = 0.02), but not in those who received prior ET for ≤6 months. Conclusion: Palbociclib has clinical activity as a single agent in women with moderately pretreated, oestrogen receptor-positive, HER2-negative advanced breast cancer. Palbociclib may have potential to reverse endocrine resistance in patients with a history of previous durable response to ET. Clinical trial information: NCT02549430